Dampak Citra dan Suasana Toko Terhadap Kepuasan Konsumen - Fakhri Mujahid Maolani; Hartelina Hartelina (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2022)
Satisfaction is part of the consumer's experience with a product or service being offered. Store image is a public perception of the company or its products, therefore for the company to have a good image is very important. The shop atmosphere is another important element in a reseller product warehouse. Retailers want to create unique store experiences that fit their target market and drive consumers to buy. The purpose of this study was to determine how much the relationship between the image of the store and the atmosphere of the grocery store in Karawang regency and to determine how much influence partially and simultaneously between the image of the store and the atmosphere of the shop on consumer satisfaction of Lotte Grosir in Karawang Regency. This research is quantitative research with descriptive and verivative research methods. The sample in this study were 100 Lotte Grosir consumers in Karawang Regency. simple random sampling, namely taking the sample randomly. The results showed that the shop image and the shop atmosphere had a strong relationship as indicated by the correlation value of 0.813. There is a partial and simultaneous influence between store image and store atmosphere on customer satisfaction at Lotte Grosir in Karawang Regency.